An analysis of perceptions of press freedom: an Islamic perspective - Sedu, Nerawi (Athens Institute for Education and Research (ATINER), 2009)
ress freedom is one of the important concepts in journalism practice P (Kent, 1972). Scholars from western countries as well as nonwestern countries have conducted many studies on the concept of press freedom from different perspectives with different emphasis (Kent, 1972; Faringer, 1991; Lee, 1991, 1997; Layton, 1993; Gunaratne, 2002). In the context of Malaysia, there were also several studies conducted on this concept but none of them analysed it from the Islamic perspective (Blackburn, 1971; Sani, Yusof, and Wok, 2003; Sani, 2005)....